An Analysis of Students’ Positive and Negative Politeness Strategies Conducted in Learning Process - Sidratul Muntaha; Uswatunnisa, Uswatunnisa; Nihla Afdaliah (STAIN Majene, 2023)
The research is derived from the politeness issue happened during teaching and learning process in the research location. The researcher found out that the students showed lack of awareness on communicating and interacting politely and formally to the teacher. This research aimed to find out the types of politeness strategies of students at SMA Negeri 1 Tinambung in learning process. The researcher applied qualitative research in order to know the students’ politeness strategies. The researcher focused on the students' 12 th-grade science at SMA Negeri 1 Tinambung. The subject of research consisted of 30–35 students from XII MIA 1 and one English teacher. The researcher did classroom observation who used politeness strategies in the classroom. In doing the classroom observation, the researcher took video to record all the activities in the classroom to see the types of politeness strategies based on Brown and Levison’s theory of Politeness Strategies. The researcher found that politeness strategies appeared in the learning process, they were positive politeness strategies. Positive politeness strategies happened to minimize the distance between the teacher and the students.